Influence of the extraction process on the antioxidant capacity of pequi pulp extracts (Research, Society and Development, 2021)
The effect of the extraction procedure on the antioxidant capacity of extracts of pequi pulp: aqueous (AQ), alcoholic (ALC) and acetomethyl (AM), obtained respectively by the solvents water, ethanol and methanol followed by acetone, was investigated. Antioxidant action was expressed by the antioxidant capacity coefficient (K) obtained by the electrochemical test (DPV) at different pH values, and in trolox equivalent (TEAC), through DPV (pH 7.15) and ABTS and DPPH spectrophotometric assays. Total carotenoid and phenolic contents were also determined. Through Principal Components and Cluster analysis, there was a greater similarity of K between AM, trolox and gallic acid, AQ and L-ascorbic acid, and ALC and β-carotene, irrespective of pH. Through Cluster analysis, the greatest K differentiation was at pH 2.20. In general, AM showed better antioxidant action (TEAC). AQ and ALC showed the highest phenolic and carotenoids content, respectively. The extraction method influenced the content of bioactive compounds in the pequi extracts and, therefore, their antioxidant capacity.